Desacralization and Commercialization of Kediri Village Okokan Tradition to Support the Tourism Industry in Bali - Wulandari, Pande Made Dwi Suci; Putra, Gede Pasek Maha; Maharani, Ni Luh Gede Putri; Yuliani, Ni Putu; Herawati, Ni Made Linda; Astawan, I Gede (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Tektekan Nangluk Merana tradition with one of its distinctive instruments, Okokan, is a ritual symbol performed in Kediri Village. The purpose of this study is to determine the form of desacralization and commercialization as well as the impact of the desacralization and commercialization of the Okokan Tradition on the tourism industry in Bali. This research uses a qualitative descriptive method. The findings show the form of desacralization and commercialization and the impact of the desacralization and commercialization of the Okokan Tradition on the tourism industry in Bali. This study concludes that the desacralization and commercialization of the Okokan Tradition in Kediri Village have positive and negative impacts, with the desacralization, the Okokan Tradition can lose its sacredness due to the various performances of the Okokan Tradition. However, from a socio-economic point of view, the commercialization of the Okokan Tradition can be used as an opportunity to increase sources of income and can be used as cultural tourism.